2020
DOI: 10.1111/exd.14093
|View full text |Cite
|
Sign up to set email alerts
|

P2Y13 and P2X7 receptors modulate mechanically induced adenosine triphosphate release from mast cells

Abstract: Subcutaneous mast cells (MCs) are vulnerable to mechanical stimulation from external environment. Thus, MCs immune function could be modulated by their mechanosensitivity. This property has been identified as the trigger mechanism of needling acupuncture, a traditional oriental therapy. Previously we have demonstrated the release of adenosine triphosphate (ATP), a stress-responsive signalling molecule, from mechanical-perturbed MCs. The current work explores its underlying mechanisms. We noticed that propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
6
19
0
Order By: Relevance
“…The activation of P2X7 receptors and associated K + efflux is a key event in the activation of inflammasome (Muñoz-Planillo et al, 2013 ). We and others have shown that mast cells express functional proinflammatory P2X7 receptors (Kurashima et al, 2012 ; Wareham and Seward, 2016 ; Nurkhametova et al, 2019 ; Shen et al, 2020 , current study). P2X7 receptor signaling was proposed to be enhanced in sensitized (primed) mast cells (Di Virgilio et al, 2018 ).…”
Section: Discussionsupporting
confidence: 56%
“…The activation of P2X7 receptors and associated K + efflux is a key event in the activation of inflammasome (Muñoz-Planillo et al, 2013 ). We and others have shown that mast cells express functional proinflammatory P2X7 receptors (Kurashima et al, 2012 ; Wareham and Seward, 2016 ; Nurkhametova et al, 2019 ; Shen et al, 2020 , current study). P2X7 receptor signaling was proposed to be enhanced in sensitized (primed) mast cells (Di Virgilio et al, 2018 ).…”
Section: Discussionsupporting
confidence: 56%
“…Due to their location, they are sensitive to mechanical stimulation from the external environment. Mast cells contain ATP which may be released as a result of AP needling [21,22]. Four pieces of evidence support this notion: Firstly, mast cell-deficient rats (with c-kit gene mutant) exhibit less mechanical analgesia than their wild-type counterparts [22].…”
Section: Local Release Of Atp By Ap Needlingmentioning
confidence: 99%
“…Secondly, mechanical stimuli lead to a rise in intracellular Ca 2+ of mast cells and release ATP in a Ca 2+ -dependent manner [23]. Thirdly, non-specific P2R antagonists or specific P2X7 or P2Y13R antagonists attenuate the release of ATP from mast cells suggesting the occurrence of an ATPinduced ATP release [21]. Fourthly, the outflow of ATP and a whole range of ATP metabolites (ADP/AMP/adenosine) have been measured in the neighboring interstitium by a microdialysis probe after AP of the Zusanli point (ST36) of mice [24,25].…”
Section: Local Release Of Atp By Ap Needlingmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, AP research in the field of purinergic signalling started to flourish and a large set of data has been accumulated on changes in purine (ATP, adenosine) concentrations, both locally and in the CNS, induced by manual acupuncture, electroacupuncture, or moxibustion [12][13][14][15][16][17]. The participation of purinergic receptors (P1: A1, A2a, A2b, A3) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], (P2: P2X2, P2X3, P2X7, P2Y1, P2Y13) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], and neuronal pathways bearing these receptors [53,54] has been confirmed in different AP-sensitive conditions (pain, inflammation, myocardial ischemia, obesity, cerebral ischemia). The functionalized acupuncture needle as a SERS (surfaceenhanced Raman spectroscopy)-active platform was developed for rapid and sensitive determination of ATP concentration [55], and led further support to the purinergic basis of AP.…”
mentioning
confidence: 99%